Музыкaльные инструменты кыргызского нaродa: лингвокультурологический экскурс - Қортaбaевa, Г. Қ; Сaрсен, Ш. М. (Journal of Oriental Studies, 2018)
The article discusses the musical instruments of the Kyrgyz people, kinds of musical instruments and provides definitions also considered.In conclusion we can say that the Kyrgyz folk music, it is embodied in the form of melodic history of the people, fully displaying his free spirit, open and friendly character and not to faint, sparkling optimism.